Studi Literatur Struktur Histologi Testis dan Epididimis Babi - Ravena J.P Kiuk; Cynthia Dewi Gaina; Filphin A Amalo (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Pigs are monogasrtic and prolific livestock (many offspring per birth), their growth is rapid and at the age of six months can be marketed. The purpose of the study was to know about histologycal struvture of the testes and epididymis of the pigs. The library study was obtained from the search and collection of various library sources from Google scholar with the help of mendeley's application. Research has shown that the testes was surrounded by a capsule made up of dense irregular connective tissue comprising three layers viz., tunica vaginalis, tunica albugenia and tunica vasculosa. The connective tissue trabeculae were extended from the capsule and divided the parenchyma of the testes into number of lobules and consisted of collagen, elastic and reticular fibers. The testicular parenchyma contains many seminiferous tubules, with each tubule consisting of a lamina propria and an epithelial layer. The seminiferous tubules consist of spermatogenic cells and Sertoli cells. There are also many Leydig cells located between the seminiferous tubules. The pigs epididymis is divided into three segments, namely, the head, body, and cauda which are composed of pseudostratified columnar epithelium and are surrounded by loose connective tissue and a layer of smooth muscle. The closer to the cauda, the smooth muscle layer gets thicker and the stereocilia gets shorter.